Selective serotonin reuptake inhibitors-associated apathy syndrome: A cross sectional study - Padala, Prasad R. (Medicine (Baltimore), 2020)
Selective serotonin reuptake inhibitors (SSRIs), commonly used to treat depression, are associated with loss of motivation, anergy, and lack of curiosity often referred collectively as apathy. However, this association has not been systematically assessed using a specific rating scale for measuring apathy syndrome. Our objective was to study the association between SSRI use and apathy syndrome. We conducted a retrospective chart review of 125 patients enrolled in an outpatient psychiatry clinic. The prevalence of apathy syndrome and its clinical significance (based on standardized assessment) were compared between patients treated and not treated with SSRIs. Apathy was assessed using the Apathy Evaluation Scale-clinician version with a score ranging 18–72 with higher score for worse apathy. A score of greater than 30 is considered clinically significant apathy. Among 119 patients, the mean apathy scores were significantly higher in those treated with SSRIs compared to those not treated with SSRIs (42.5 ± 9.2 vs 31.3 ± 6, P < .0001). The SSRI group also had a significantly higher percentage of patients with clinically significant apathy (92% vs 61%, P < .0001). Use of all SSRIs was associated with the presence of apathy. Apathy was seen in all mental health diagnostic categories with highest Apathy evaluation scale-clinician version scores in those with dementia. SSRI use may be associated with higher rates of apathy syndrome. Clinicians should specifically inquire about iatrogenic apathy syndrome when evaluating patients on an SSRI if there is suspicion of loss of motivation. Limitations of this study included retrospective nature of this study, and that majority of the sample was males. Prospective studies are needed to elucidate information regarding the prevalence, etiology, and treatment response for SSRI-associated apathy syndrome.